Financing the Transformation of Food Systems Under a Changing Climate - Millan, Alberto; Limketkai, Benhan; Guarnaschelli, Serena (2019)
The global food system will need to produce food more efficiently and sustainably to achieve the Sustainable Development Goals (‘SDGs’) and meet the 2°C climate commitments of the Paris Agreement. As climate change affects food systems, governments, food and agriculture companies, and public and private investors need to better identify and address the numerous climate-related risks they face. This can be an inflection point to seize the new investment opportunities that the transformation to low-carbon and resilient food systems presents. This will require addressing core market failures to unlocking private sector financing from food and agriculture companies, domestic and international financial institutions, and specialized investors. Against this backdrop, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and its partners propose three solutions: i) Create investment opportunities in the transformation of food systems; ii) Accurately assess risk and deploy appropriate risk-mitigating mechanisms; iii) Intermediate/match to the respective risk-return profiles of different sources of private capital. In addition, the paper provides a set of recommended strategies for each potential solution, as well as a detailed roadmap on how to finance the transformation of food systems under a changing climate.